BI SOLUTIONS AND MULTI-AGENT PLATFORMS FOR MODELING EDUCATIONAL PROCESSES (International Conference on Educational Discoveries and Humanities, 2025)
Modern educational systems require the development of effective approaches to the management of educational processes and resources. In this regard, modeling and simulation based on multi-agent systems is becoming increasingly relevant for creating solutions in the field of decision support and educational process management. This article proposes a solution for processing simulation model data, namely output data and real data used to optimize educational routes and interactions between educational modules.